The SASE1 X‐ray beam transport system. (17th April 2019) - Sinn, H.; Dommach, M.; Dickert, B.; Di Felice, M.; Dong, X.; Eidam, J.; Finze, D.; Freijo-Martin, I.; Gerasimova, N.; Kohlstrunk, N.; La Civita, D.; Meyn, F.; et al.
Abstract : The beam transport system of the European XFEL SASE1 beamline is described together with experiences gained during the first user runs. Abstract : SASE1 is the first beamline of the European XFEL that became operational in 2017. It consists of the SASE1 undulator system, the beam transport system, and the two scientific experiment stations: Single Particles, Clusters, and Biomolecules and Serial Femtosecond Crystallography (SPB/SFX), and Femtosecond X‐ray Experiments (FXE). The beam transport system comprises mirrors to offset and guide the beam to the instruments and a set of X‐ray optical components to align, manipulate and diagnose the beam. The SASE1 beam transport system is described here in its initial configuration, and results and experiences from the first year of user operation are reported.